Cohabitation before marriage? An examination of pre-acquisition alliance partnerships and merger outcomes - Yu, Han; He, Zhaozhao (Review of Quantitative Finance and Accounting, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eco; peer-reviewed

Firm risk and proxy fights: Evidence from SOX - Chen, Fang; Huang, Jian; Yu, Han (Accounting and Finance Research, 2018)
The Sarbanes Oxley Act of 2002 (SOX) is documented to curb executive risk-taking and firm risk. Utilizing SOX as an exogenous shock on firm risk, we find that proxy fight threats are positively related to a firm’s total risk and idiosyncratic risk. Specifically, although firm risk generally decreases post-SOX, high proxy fight threats mitigate this change in firm risk. We also find that although firms adopt more conservative policies such as decreasing their leverage and payout post-SOX, these changes are mitigated by proxy fight threats. In sum, our findings indicate that proxy fights act as an external disciplinary mechanism, encourage executive risk-taking, and increase firm risk.
0 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.fin; peer-reviewed

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
1 citations (Crossref) [2023-10-31] tex.ids: chenIntraindustryEffectsProxy2020, lens.org/134-505-396-626-539 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85070373506 tex.type: [object Object] type: Article
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed